1993
DOI: 10.1042/bj2910447
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ pools in Jurkat T-lymphocytes

Abstract: Jurkat T-lymphocytes comprise at least four intracellular Ca2+ pools. Pool I was agonist-sensitive and contained 23 +/- 8% (n = 18) of the total Ca(2+)-storage capacity, as shown in intact cells in the presence of EGTA. The time courses of the agonist-induced formation of Ins(1,4,5)P3 and of the Ca2+ release from pool I were nearly superimposable, indicating that the agonist-sensitive pool I is emptied by Ins(1,4,5)P3. Likewise, in permeabilized cells, the size of the Ins(1,4,5)P3-sensitive Ca2+ pool I was 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 23 publications
5
129
1
Order By: Relevance
“…IP4 is a precursor for several higher order inositol polyphosphates, some of which are generated in TCR-stimulated T cells (49,50). Their physiological roles are largely undefined (9), but recent studies in yeast suggest functions in regulating chromatin remodeling (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…IP4 is a precursor for several higher order inositol polyphosphates, some of which are generated in TCR-stimulated T cells (49,50). Their physiological roles are largely undefined (9), but recent studies in yeast suggest functions in regulating chromatin remodeling (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Rat antigen-specific T cell clones were obtained from lymph node preparations of immunized Lewis rats. Stimulation, expansion, and culture of specific rat T cells were conducted under conditions as described (44). Details concerning generation of MBP-specific CD4 ϩ T cells (TMBP) retrovirally engineered to express the marker gene EGFP are provided in the SI Methods.…”
Section: High-affinity [ 3 H]ryanodinementioning
confidence: 99%
“…Both Jurkat T lymphoma and rat TMBP cells were loaded with Fura-2/AM (Calbiochem) as described (44) and kept in the dark at room temperature until use. Intracellular Ca 2ϩ ([Ca 2ϩ ]i) was determined in suspensions of Fura-2-loaded rat T MBP cells which had been preincubated with BZ194 or DMSO at the indicated concentrations for at least 8 h in a Hitachi F-2000 fluorometer as described previously (46).…”
Section: High-affinity [ 3 H]ryanodinementioning
confidence: 99%
“…The major pathway of InsP 6 dephosphorylation in mammals is not well-characterized, but several InsP 5 isomers are generated (757), and Ins(l,2,3,4)P 4 / Ins(l,2,3,6)P 4 , Ins(l,2,3)P 3 and ïns(l,2)P 2 / Ins(2,3)P 2 also appear to be formed during the degradation to free Ins (93,150,158). There is some evidence that the activity of this catabolic pathway may change both during the cell cycle, or upon cell differentiation (131,(150)(151)(152), but the cause/effect relationship between these events is not known. Some workers have reported that InsP 6 , or one of its metabolites, has an anti-neoplastic action (759).…”
Section: Inspmentioning
confidence: 99%
“…Cellular levels of InsP 6 do not respond dramatically to short-term receptor activation (see above). However, they do rise and fall at certain points in the cell-cycle and during cellular differentiation (131,(150)(151)(152), when there are also dramatic changes in vesicle trafficking processes (753). It is possible that extracellular agonists might also act upon InsP 6 in a more subtle manner, by perhaps altering its distribution between cellular membranes (see above) and the cytosol.…”
Section: Inspmentioning
confidence: 99%